Efficacy of Computer Assisted Language Learning for Self-Learners of Engineering - Yasaswini chowdary, K.; Vanaja Reddy, G. (Journal of Engineering Education Transformations, 2025)
Each year teachers encounter learners with distinct personalities, with diverse temperaments (as learners may come from different pockets of a country), and with high aspirations. Meeting these demands may throw a challenge to the teaching community. In this volatile environment teacher has to constantly reinvent new approaches of teaching and redesign methods of teaching, to help the learner. Hence it is being impractical to meet by the traditional methods. Further, the tradition has also shifted from a restricted classroom to virtual classroom, physical teacher to a virtual teacher. Widespread use of technology has led to revolutionary changes in the process of language acquisition .Especially, computer assisted language learning (CALL) acts as a juggler in the hands of a graduate learner. CALL offers innumerable opportunities to learn beyond the class room environment. . This paper focuses on the Inevitability of Internet - based Computer Assisted Language Learning (CALL) for self-learners of Engineering in the global age. This paper also examines the expeditious acquisition of language by using CALL in contrast with the conventional classroom setting.